Method for manufacturing piezoceramic fiber composite component and component
Patent Information
- Application Number
- CN202610953538.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-13
AI Technical Summary
然而,在制备得到的压电纤维层进行封装之前,涉及到上下两个电极层以及中间压电纤维层的排列对准、电极层与压电纤维层之间有机物层厚度的控制、以及有机物中气泡的去除等问题
本发明提供的压电陶瓷纤维复合材料器件的制备方法,通过采用定位治具配合定位垫片实现压电陶瓷纤维层与电极层的精确层间定位,有效解决了各层对准不良导致的性能退化和短路问题;通过丝网印刷技术涂敷有机物胶液,实现了有机物层厚度的精确控制,避免了极化不充分或局部击穿的问题;通过在真空环境下进行多段温度与压力控制的热压固化封装,有效去除了有机物中的气泡,防止极化击穿,提高了器件的极化效果;最后通过油浴极化处理使器件获得良好的压电性能。该方法整体上提高了压电陶瓷纤维复合材料器件的制备良品率和性能稳定性。
Smart Images

Figure CN122909995A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of materials and functional device fabrication, and in particular to a method for fabricating a piezoelectric ceramic fiber composite material device and the device thereof. Background Technology
[0002] Piezoelectric ceramic materials, due to their excellent properties and ease of fabrication, can achieve the conversion between mechanical energy and electrical energy through the piezoelectric effect, and have been widely used in ultrasonic motors, energy harvesting, piezoelectric sensors, non-destructive testing, and other fields. However, piezoelectric ceramics are characterized by high brittleness, high density, and small deformation, which limits their application in curved structures or high-strain scenarios. To overcome these limitations, piezoelectric composite materials have been extensively researched and developed.
[0003] Piezoelectric fiber composites can effectively improve the aforementioned problems while retaining the strong driving force characteristics of piezoelectric ceramics. These composites typically use interdigitated electrodes to encapsulate unidirectional and uniformly distributed piezoelectric fibers. The interdigitated electrode structure effectively utilizes the piezoelectric coefficient of the fibers, resulting in a composite material with a large driving strain while reducing polarization and driving voltage. Compared to traditional piezoelectric ceramics, piezoelectric fiber composites offer advantages such as high driving force, thinness, light weight, and high flexibility, enabling significant bending and torsion, and can be bonded to complex structural surfaces. In recent years, piezoelectric fiber composites have shown broad application prospects as actuators in large-scale intelligent structures, such as drone propulsion, helicopter rotor health monitoring, flutter suppression, and smart wearables.
[0004] Currently, mature fabrication processes for piezoelectric fiber layers include direct cutting and lamination, cutting and filling, and cutting and stacking. Among these, the cutting and filling and cutting and stacking methods are more suitable for mass production in engineering applications. However, before encapsulating the fabricated piezoelectric fiber layer, issues arise regarding the alignment of the upper and lower electrode layers and the intermediate piezoelectric fiber layer, the control of the thickness of the organic layer between the electrode layer and the piezoelectric fiber layer, and the removal of air bubbles from the organic material.
[0005] The aforementioned issues can lead to suboptimal material encapsulation results. For example, poor alignment between layers can easily cause performance degradation or even short circuits; improper control of the organic layer thickness may result in insufficient polarization or localized breakdown; and residual air bubbles in the organic material can easily cause polarization breakdown, making it difficult for the device to be effectively polarized. Therefore, in the fabrication process of piezoelectric fiber composite devices, the alignment issues of each layer during encapsulation and the control of the organic layer between the ceramic fiber layer and the electrode layer will affect the polarization of the device, potentially leading to reduced yield and performance degradation. Summary of the Invention
[0006] In view of the shortcomings of the prior art described above, the purpose of this invention is to provide a method and device for preparing piezoelectric ceramic fiber composite material devices, which can quickly and effectively perform positioning, control the thickness and consistency of organic layers, and effectively reduce the formation of defects such as bubbles or voids within and between organic layers, thereby ensuring the successful encapsulation of the prepared piezoelectric fiber device.
[0007] To achieve the above objectives, the present invention adopts the following technical solution.
[0008] In a first aspect, the present invention provides a method for preparing a piezoelectric ceramic fiber composite material device, which adopts the following technical solution: Obtain a piezoelectric ceramic fiber layer; A positioning fixture and positioning pads are used to position the piezoelectric ceramic fiber layer and the electrode layer between layers; An organic adhesive was applied between the piezoelectric ceramic fiber layer and the electrode layer using screen printing technology. Thermopressing and curing encapsulation under multi-stage temperature and pressure control in a vacuum environment yields the encapsulated device; and The packaged device is subjected to oil bath polarization treatment.
[0009] Furthermore, in the above preparation method, the piezoelectric ceramic fiber layer is obtained by a cutting and filling method or a cutting and laminating method, and the piezoelectric ceramic fiber layer is composed of ceramic fibers and organic materials spaced apart, with a thickness of 0.1 mm to 1 mm.
[0010] Furthermore, in the above preparation method, the electrode layer is a polyimide interdigitated electrode, which is placed on a polyester film. The polyester film has positioning holes, and the electrodes are fixed by positioning pins to ensure that the upper and lower electrodes are aligned.
[0011] Furthermore, in the above preparation method, there are two positioning pads, which form a central groove by positioning pins distributed on both sides of the electrode, and the piezoelectric ceramic fiber layer is placed in the central groove.
[0012] Furthermore, in the above preparation method, the organic adhesive is any one of epoxy resin, polyester resin, or phenolic resin.
[0013] Furthermore, in the above preparation method, the screen printing technology uses a screen mesh count of 50 to 300.
[0014] Furthermore, in the above preparation method, the positioning fixture includes two metal plates, upper and lower, and a high-temperature resistant resilient plate is provided between the metal plates and the electrode layer.
[0015] Furthermore, in the above preparation method, before hot pressing and curing encapsulation, a vacuum treatment is performed, with the vacuum negative pressure set to -0.080MPa to -0.096MPa.
[0016] Furthermore, in the above preparation method, after vacuum treatment, multi-stage heating and pressure setting treatment is carried out for staged curing to ensure that air bubbles in the organic adhesive and between layers are eliminated while the device is encapsulated.
[0017] Furthermore, in the above preparation method, the polarizing medium for the oil bath polarization treatment is silicone oil, the polarization electric field is between 1.50 kV / mm and 3.30 kV / mm, the polarization time is between 10 min and 30 min, and the polarization temperature is between 20℃ and 80℃.
[0018] Secondly, the present invention provides a piezoelectric ceramic fiber composite material device, which adopts the following technical solution: A piezoelectric ceramic fiber composite material device is prepared by any one of the preparation methods described in the first aspect above.
[0019] In summary, compared with the prior art, the present invention has at least one of the following beneficial technical effects: The method for fabricating piezoelectric ceramic fiber composite devices provided by this invention achieves precise interlayer positioning of the piezoelectric ceramic fiber layer and the electrode layer by using a positioning fixture and positioning pads, effectively solving the performance degradation and short circuit problems caused by misalignment of each layer; the application of organic adhesive through screen printing technology enables precise control of the organic layer thickness, avoiding problems such as insufficient polarization or local breakdown; multi-stage temperature and pressure controlled thermopressing and curing encapsulation in a vacuum environment effectively removes air bubbles in the organic material, preventing polarization breakdown and improving the polarization effect of the device; finally, oil bath polarization treatment gives the device good piezoelectric properties. This method comprehensively improves the yield and performance stability of piezoelectric ceramic fiber composite devices. Attached Figure Description
[0020] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 The image shown is a scanning electron microscope image of the prepared piezoelectric fiber layer, which is composed of piezoelectric ceramic fibers and organic materials as spacers.
[0022] Figure 2The diagram shows the designed polyimide upper and lower electrode layers, including three positioning holes on both sides of the electrode layers located on the polyester film.
[0023] Figure 3 The diagram shows the combination of the electrode layer, two positioning pads, and the piezoelectric ceramic fiber layer. 1 is the electrode layer, 2 is the piezoelectric ceramic fiber layer, and 3 and 4 are the positioning pads.
[0024] Figure 4 The diagram shows the electrode layer, two positioning pads, and piezoelectric ceramic fiber layer after separation. 1 is the electrode layer, 2 is the piezoelectric ceramic fiber layer, and 3 and 4 are the positioning pads.
[0025] Figure 5 The diagram shows the free strain performance of piezoelectric fiber composite devices of the same specifications prepared by SmartMaterials and the method of this invention under a certain driving voltage. Detailed Implementation
[0026] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application. Furthermore, it should be understood that the specific embodiments described herein are only for illustration and explanation of this application and are not intended to limit this application.
[0027] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments of this application. Furthermore, the descriptions of each embodiment in the following embodiments have their own emphasis; for parts not described in detail in a certain embodiment, please refer to the relevant descriptions in other embodiments.
[0028] The method steps described in this embodiment of the invention can be executed in the order described in the specific implementation, or the execution order of each step can be adjusted according to actual needs, provided that the technical problem can be solved. These are not listed one by one here.
[0029] This invention provides a method for preparing a piezoelectric ceramic fiber composite material device, comprising: Piezoelectric ceramic fiber layers with good batch consistency can be obtained through cutting-filling or cutting-layering methods, consisting of ceramic fibers interspersed with organic materials, such as... Figure 1 As shown; The prepared PI electrode is placed on a PET film. Three holes are punched on both sides of the PI electrode film for positioning with the corresponding fixture. The upper and lower electrodes are as follows: Figure 2 As shown; A 1-2mm thick high-temperature resistant and resilient plate is placed between the metal fixture plate and the electrode. An electrode layer is fixed through three holes, two corresponding positioning plates are placed, and then the piezoelectric ceramic fiber layer is placed in the central groove. Figure 3 and 4 As shown; An organic adhesive is applied between the piezoelectric fiber layer and the upper and lower electrode layers, and the thickness of the adhesive is controlled by screen printing. After the upper and lower metal plates of the fixture are closed, it is placed between the hot press plates and vacuumed. Set the pressure and temperature, heat and pressurize in multiple stages, and after the program is completed, remove the packaged piezoelectric ceramic fiber composite material device. After welding wires to the positive and negative electrodes of the device, oil bath polarization is performed to obtain the corresponding piezoelectric fiber composite material device.
[0030] The following provides a detailed explanation of each step in the above preparation method.
[0031] The piezoelectric ceramic fiber layer can be obtained by a cutting-filling method or a cutting-layering method, and is composed of ceramic fibers and organic materials spaced apart, with a thickness of 0.1 mm to 1 mm. For example... Figure 1 As shown, the piezoelectric ceramic fiber layer exhibits a regular striped structure. The dark stripes represent piezoelectric ceramic fibers, while the light-colored areas represent organic matter filling the spaces between the ceramic fibers. The piezoelectric ceramic fibers and organic matter are arranged in a unidirectional and uniform manner.
[0032] The electrode layer may be a polyimide (PI) interdigitated electrode, which is placed on a polyester (PET) film. For example... Figure 2 As shown, the polyester film has positioning holes located on both sides of the electrode layer along its length, totaling three holes arranged in a triangle. Positioning pins are used to fix the electrodes, ensuring alignment of the upper and lower electrodes. The upper and lower electrodes can be mirror-symmetrically arranged to effectively cover the piezoelectric ceramic fiber layer during encapsulation.
[0033] The positioning fixture may include two metal plates, upper and lower. A high-temperature resistant, resilient material, such as a high-temperature resistant silicone foam board, may be provided between the metal plates and the electrode layer to ensure effective encapsulation of the piezoelectric ceramic fiber composite device under thermo-pressure vacuum conditions. Two positioning pads may be used, such as… Figure 3 and Figure 4As shown, positioning pads 3 and 4 form a central groove by means of positioning pins distributed on both sides of electrode layer 1. The piezoelectric ceramic fiber layer 2 is placed within this central groove to ensure that it is centered between the two electrode layers. In some aspects, the thickness of positioning pads 3 and 4 can be comparable to the thickness of the piezoelectric ceramic fiber layer 2 to ensure flatness and alignment accuracy between layers during encapsulation.
[0034] The organic adhesive can be any one of thermosetting resins such as epoxy resin, polyester resin, or phenolic resin.
[0035] The screen printing technology uses a mesh size of 50 to 300. Screen printing can control the consistency of the organic adhesive used each time, ensuring that the thickness of the two polymer layers is uniform and consistent, and ensuring the consistency of the organic layer of the device each time.
[0036] In the vacuuming process, a vacuuming process can be performed before hot pressing and curing encapsulation. The vacuum negative pressure can be set to -0.080MPa to -0.096MPa.
[0037] Regarding multi-stage temperature and pressure control, while maintaining vacuum, multiple temperature and pressure adjustments can be made to ensure device encapsulation while eliminating air bubbles in the organic adhesive and between layers. In some cases, the multi-stage temperature and pressure settings can be as follows: First stage temperature set at 30–40℃, pressure at 100 kg, holding for 5–10 minutes; second stage temperature set at 50–60℃, pressure at 300 kg, holding for 10–15 minutes; third stage temperature set at 80–90℃, pressure at 500 kg, holding for 30–60 minutes; fourth stage temperature set at 50–60℃, pressure at 400 kg, holding for 5–10 minutes; fifth stage temperature set at 40–50℃, pressure at 200 kg, holding for 3–6 minutes; sixth stage temperature set at 30℃, pressure at 100 kg, holding for 1–5 minutes.
[0038] The polarization medium for the oil bath polarization treatment can be silicone oil, the polarization electric field can be between 1.50 kV / mm and 3.30 kV / mm, the polarization time can be between 10 min and 30 min, and the polarization temperature can be between 20℃ and 80℃.
[0039] The piezoelectric ceramic fiber composite device prepared by the above method includes a piezoelectric ceramic fiber layer, electrode layers located on the upper and lower sides of the piezoelectric ceramic fiber layer, and an organic layer located between the piezoelectric ceramic fiber layer and the electrode layer. The piezoelectric ceramic fiber layer is composed of ceramic fibers and organic materials spaced apart, arranged in a unidirectional and uniform manner. The electrode layer can be polyimide interdigitated electrodes, with the upper and lower electrodes arranged in a mirror-symmetrical configuration. The organic layer is coated using screen printing technology, resulting in a uniform thickness. In some aspects, the device undergoes multi-stage temperature and pressure controlled thermopressing and curing encapsulation under vacuum, achieving high alignment accuracy between layers and virtually no air bubbles remaining in the organic layer. In other aspects, the device exhibits excellent piezoelectric properties after oil bath polarization treatment, with a free strain coefficient exceeding 1.0 με / V, higher than the 0.7–0.9 με / V of commercial piezoelectric fiber composite devices.
[0040] Example The piezoelectric ceramic material in this embodiment is composed of lead zirconate titanate (Pb(Zr,Ti)O3,PZT). The piezoelectric ceramic fiber composite device is prepared using the present invention, and the specific process is as follows.
[0041] 1. Using a cutting and filling method, the ceramic block is grooved and filled with organic adhesive, followed by wire cutting to obtain piezoelectric ceramic fiber layers of uniform thickness in batches. The widths of the organic material and ceramic fibers are 75±1μm and 376±3μm, respectively. Figure 1 As shown.
[0042] 2. Fabricate upper and lower PI interdigitated electrodes, such as... Figure 2 As shown, the positive and negative electrodes are interdigitated with a spacing of 0.5 mm. The three holes are all 4 mm in diameter and are positioned as shown in the figure.
[0043] 3. Place a silicone pad and a PI electrode sequentially on the lower surface of the metal fixture. Use screen printing to coat the space between the piezoelectric ceramic fiber layer and the electrode layer with an organic adhesive. Then, place the piezoelectric ceramic fiber layer, the PI electrode, and the silicone pad sequentially. Close the upper surface of the metal fixture and place it between the hot-pressing parallel plates.
[0044] 4. Close the cavity and evacuate the vacuum. Set the vacuum negative pressure to -0.091 MPa.
[0045] Set multiple pressure, temperature, and holding time settings. The first setting is 30℃, 100Kg, and a holding time of 5 minutes; the second setting is 60℃, 300Kg, and a holding time of 12 minutes; the third setting is 85℃, 500Kg, and a holding time of 40 minutes; the fourth setting is 60℃, 400Kg, and a holding time of 6 minutes; the fifth setting is 44℃, 200Kg, and a holding time of 4 minutes; and the sixth setting is 30℃, 100Kg, and a holding time of 3 minutes.
[0046] 5. Once the program is complete, the cavity will open automatically, allowing you to remove the encapsulated piezoelectric ceramic fiber composite material device.
[0047] 6. After welding wires to the positive and negative electrodes of the device, oil bath polarization is performed. The polarization temperature is 25℃, the polarization electric field is between 2.7kV / mm, and the polarization time is 15min to obtain the corresponding piezoelectric fiber composite material device.
[0048] 7. Attach a standard strain gauge to the center of the piezoelectric fiber composite device and perform free strain testing. The free strain performance under different applied voltages is as follows: Figure 5 As shown in (c), at the maximum voltage of 1200V, the free strain value can reach ~1300με and the free strain coefficient is as high as 1.08με / V, which is higher than the 0.7~0.9με / V of commercial piezoelectric fiber composite devices.
[0049] Comparative Example 1 The piezoelectric ceramic material used in Comparative Example 1 is PZT material. No positioning fixture or hot-pressing vacuum equipment is used. No positioning tools are used in the preparation process. Alignment is done by visual observation. Instead, a vacuum oven is used to prepare the device. The specific process is as follows.
[0050] 1. Place the obtained piezoelectric fiber layer on the polyimide lower electrode through the human eye, apply an organic adhesive between the two layers, cure in the air for 10 minutes, and then place silicone sheets on the top and bottom.
[0051] 2. Secure the silicone sheet to the two metal plates with bolts, tighten it with a certain force, place it in a vacuum oven, vacuum it, set the temperature to 60℃, keep it at that temperature for 2 hours, and then take it out.
[0052] 3. After removing the silicone pad, apply organic adhesive, place the polyimide top electrode, and let it cure in the air for 10 minutes before placing the silicone sheet on top.
[0053] 4. Secure the silicone sheet to the two metal plates with bolts, tighten it with a certain force, place it in a vacuum oven, vacuum it, set the temperature to 80℃, keep it at that temperature for 4 hours, and then take it out after it cools down to room temperature naturally.
[0054] 5. After welding wires to the positive and negative electrodes of the device, oil bath polarization is performed at a polarization temperature of 25℃. The polarization voltage is increased slowly. When the polarization electric field increases to 2.2kV / mm, the leakage current is too large, causing the piezoelectric fiber composite material to break down, and the polarization voltage is difficult to increase further.
[0055] 6. By observing the state of each layer of the device and the location of the breakdown point, it was found that the above method can easily cause the layers to slide in the vacuum oven, resulting in uneven actual distance between the interpolation electrodes and shorter interpolation positive and negative electrode distances in some local locations; polarization breakdown points mostly occur at the edges of the piezoelectric fiber layer where there are air bubbles, that is, the air bubbles between the layers are difficult to remove.
[0056] 7. Repeat the above steps. Under the condition that the leakage current does not lead to breakdown, with a polarization temperature of 25°C, a polarization electric field of 2.4kV / mm, and a polarization time of 20min, the corresponding piezoelectric fiber composite material device has a free strain value of less than 400με at 1200V, which is far lower than the free strain value of the present invention.
[0057] Comparative Example 2 The piezoelectric ceramic material in Comparative Example 2 is PZT material. Unlike the present invention, vacuuming is not performed during the curing stage after the material is placed in the hot press. Other steps are basically the same.
[0058] Free strain properties under different applied voltages, such as Figure 5 As shown in (b), at the maximum voltage of 1200V, the free strain value can reach ~936με, and the free strain coefficient is 0.78με / V.
[0059] Comparative Example 3 The piezoelectric ceramic fiber composite device in Comparative Example 3 is a commercially available device of the same specifications from SmartMaterials and is used solely for testing and comparison.
[0060] Free strain properties under different applied voltages, such as Figure 5 As shown in (a), at the maximum voltage of 1400V, the free strain value can reach ~1192με, and the free strain coefficient is 0.85με / V.
[0061] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a piezoelectric ceramic fiber composite material device, characterized in that, include: Obtain a piezoelectric ceramic fiber layer; A positioning fixture and positioning pads are used to position the piezoelectric ceramic fiber layer and the electrode layer between layers; An organic adhesive was applied between the piezoelectric ceramic fiber layer and the electrode layer using screen printing technology. The encapsulated device is obtained by thermopressing and curing under multi-stage temperature and pressure control in a vacuum environment. as well as The packaged device is subjected to oil bath polarization treatment.
2. The preparation method according to claim 1, characterized in that, The piezoelectric ceramic fiber layer is obtained by a cutting and filling method or a cutting and laminating method. The piezoelectric ceramic fiber layer is composed of ceramic fibers and organic materials spaced apart, and has a thickness of 0.1 mm to 1 mm.
3. The preparation method according to claim 1, characterized in that, The electrode layer is a polyimide interdigitated electrode, which is placed on a polyester film. The polyester film has positioning holes, and the electrodes are fixed by positioning pins to ensure that the upper and lower electrodes are aligned.
4. The preparation method according to claim 1, characterized in that, There are two positioning pads, which form a central groove by positioning pins distributed on both sides of the electrode, and the piezoelectric ceramic fiber layer is placed in the central groove.
5. The preparation method according to claim 1, characterized in that, The organic adhesive is any one of epoxy resin, polyester resin, or phenolic resin.
6. The preparation method according to claim 1, characterized in that, The screen printing technology uses a screen mesh count of 50 to 300.
7. The preparation method according to claim 1, characterized in that, The positioning fixture includes two metal plates, upper and lower, with a high-temperature resistant resilient plate material between the metal plates and the electrode layer.
8. The preparation method according to claim 1, characterized in that, Before hot-pressing and curing, a vacuum process is performed, with the vacuum negative pressure set to -0.080MPa to -0.096MPa.
9. The preparation method according to claim 1, characterized in that, After vacuuming, multi-stage heating and pressure settings are applied for phased curing to ensure device encapsulation while eliminating air bubbles in the organic adhesive and between layers.
10. The preparation method according to claim 1, characterized in that, The polarization medium for the oil bath polarization treatment is silicone oil, the polarization electric field is between 1.50 kV / mm and 3.30 kV / mm, the polarization time is between 10 min and 30 min, and the polarization temperature is between 20℃ and 80℃.
11. A piezoelectric ceramic fiber composite material device, characterized in that, It is prepared by any one of the preparation methods according to claims 1 to 9.